Human Resource Management and Impact on Performance on Employee in Kosovo Tourism - KRASNIQI, Avni Ekrem (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021DO - 10.14505//jemt.v12.4(52).19, 2021)
This research presents the impact of human resource management on the performance of employees in tourist centers in Kosovo.This research also measures the badness of foreign tourists with the tourist services that are offered. Employee performance is one of the factors that dictate the flow of tourism work in any country of the world, especially it depends on the forms of human resource management, ie how attentive managers are in creating a working climate and achieving performance.This research was conducted for this purpose, and involved a total of 200 workers of different levels and 230 foreign trusses, through a well-structured questionnaire, and its scientific impact lies in the fact that it helps tourist centers to improve or increase appropriate forms of human resource management. The multiple regression model was used to analyze the results, while the statistical program is SPSS.The results show that the performance of workers of tourist places in Kosovo depends directly on their motivation (p-value = M1: 0.006 / M2: 0.034) and their satisfaction with the workplace and the conditions offered (p-value = 0.047), whereas no impact of cooperation and communication with the performance of workers was found. Based on the results, it is confirmed that tourists in Kosovo have expressed a high level of satisfaction with the structure and tourist services provided.